Transparent ceramics of yttrium-aluminum garnet (Y₃Al₅O₁₂) from nanocrystalline powders obtained by co-precipitation - Baumer, V.N.; Vovk, E.A.; Vovk, O.M.; Deineka, T.G.; Kosmyna, M.B.; Mateychenko, P.V.; Puzikov, V.M.; Sergienko, Z.P.; Tolmachev, A.V.; Shekhovtsov, A.N.; Yavetskiy, R.P. (Functional Materials, 2008)
Nanosized powders of yttrium-aluminum garnet Y₃Al₅O₁₂, (YAG) have been obtained by chemical co-precipitation. The effect of the powder structure and morphology on the compactibility and sinterability has been studied. The optimal combination of these properties has been found in the YAG powder having the average grain size of 80 nm synthesized at 1200°C. Using the vacuum sintering at 1750°C, the transparent Y₃Al₅O₁₂ ceramics has been obtained having the density 99.9% of theoretical value and the transmission coefficient 60% in the wavelength range of 400 to 800 nm. Методом хімічного співосадження синтезовано нанорозмірні порошки ітрійалюмінієвого гранату Y₃Al₅O₁₂ (ІАГ). Вивчено вплив структури та морфології порошків на їх пресуємість та спікливість. Встановлено, що оптимальні сполучення цих характеристик має порошок ІАГ із середнім розміром зерна 80 нм, синтезований при температурі 1200°С. Методом вакуумного спікання при 1750°С одержано прозору кераміку Y₃Al₅O₁₂ із щільністю 99,9% від теоретичної та коефіцієнтом пропускання 60% в області довжин хвиль 400-800 нм. Методом химического соосаждения получены наноразмерные порошки иттрий-алюминиевого граната Y₃Al₅O₁₂ (ИАГ). Изучено влияние структуры и морфологии порошков на их прессуем ость и спекаем ость. Установлено, что оптимальным сочетанием этих характеристик обладает порошок ИАГ со средним размером зерна 80 нм, синтезированный при температуре 1200°С. Методом вакуумного спекания при 1750°С получена прозрачная керамика Y₃Al₅O₁₂ с плотностью 99,9% от теоретической и коэффициентом пропускания 60% в области длин волн 400-800 нм.